Miniature design of T-Shaped frequency Reconfigurable antenna for S-Band Application using Switching Technique - Omar El Maleky; Farid Ben Abdelouahab; Mohammad Essaaidi; Nasri Abdelfatah (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The article presents a miniature antenna with a simple geometry and a simple approach for reconfiguration. In order to make the T-shaped antenna frequency reconfigurable, we integrated Switches in specific positions. The location of the switches is determined following a study of the distribution of the surface currents of the suggested antenna. Indeed, we found that the insertion of switches in places where the concentrations of surface currents are high is irrelevant. In fact, to redirect current flow, the PIN diodes or RF Switch must be placed in positions where the distribution of the surface currents is of low concentration. These locations facilitate the establishment of new trajectories of the flux of current. As a result, a miniature tunable antenna dimension 20mm*20mm*1.6mm printed on FR4 substrate with 4.4 permittivity and with  0.04 loss tangent,   the antenna  can be adopted in many communication devices in view of its small size, its low manufacturing cost and performance on frequency sweep, the antenna operates in S-Band with an acceptable band and gain. The antenna is simulated and optimized using CST Microwave Studio.